Apparatus for connection to public telecommunications systems using the Digital Access Signalling System No. 2 (DASS 2) via a 2048 kbit/s CCITT Recommendation G.703 interface. General requirements Part 1, (15th October 1997) - British Standards Institution,
No abstract available